Spectral inclusion properties of the numerical range in a space with an indefinite metric - Wu, Deyu; Chen, Alatancang (Linear algebra and its applications, 2011)
In this paper the numerical range of operators (possibly unbounded) in an indefinite inner product space is studied. In particular, we show that the spectrums of bounded positive operators (or the spectrum of unbounded uniformly I -positive operators) are contained in the closure of the I -numerical range.